Mechanical Anisotropy of Birch (Betula pubescens), Scots Pine (Pinus sylvestris L.) and Norway Spruce (Picea abies) - Awoyemi, Lawrence (Indian Forester, 2006)
In order to ensure a more effective use of wood as a structural material through the application of load on the plane of maximum strength it is essential to establish the mechanical anisotropy of individual species rather than assuming all wood to be stronger radially than tangentially. The mechanical anisotropy of wood from three species viz. Birch (Betula pubescen), Scots pine(Pinus sylvestri L.) and Norway spruce (Picea abie) was determined. The wood of Picea abies is anisotropic being stronger tangentially than radially while Betula pubescens and Pinus sylvestris are orthotropic. It is concluded that not all species are significantly mechanically anisotropic and that the plane of maximum strength varies from species to species.